2015
DOI: 10.1111/1742-6723.12335
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported preparedness of New Zealand acute care providers to mass emergencies before the Canterbury Earthquakes: A national survey

Abstract: Almost half of New Zealand acute healthcare providers have no training in dealing with mass emergency events. Training and general awareness of the role during a mass emergency response were the main factors associated with strong self-reported preparedness of acute care providers. The apparent efficacy of training allied to lack of availability means that it should be a national priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…For this reason, it is difficult to say how such a reaction would actually look in the event of other incidents. For example, a study in New Zealand showed that despite a low self-reported preparedness among acute care providers, the healthcare service was found to have "responded well to extraordinary circumstances" in the Canterbury earthquakes in 2010 and 2011 [21]. On the other hand, numerous studies show that healthcare workers, confident of their own high competences, are more likely to react effectively in real crises than workers who perceive their competences as low [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is difficult to say how such a reaction would actually look in the event of other incidents. For example, a study in New Zealand showed that despite a low self-reported preparedness among acute care providers, the healthcare service was found to have "responded well to extraordinary circumstances" in the Canterbury earthquakes in 2010 and 2011 [21]. On the other hand, numerous studies show that healthcare workers, confident of their own high competences, are more likely to react effectively in real crises than workers who perceive their competences as low [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…have been published. [3][4][5][6][7][8][9][10][11][12][13][14] Most studies were surveys conducted in North America, Europe, and Australasia and many focused on chemical, biological, radiological, nuclear, and explosive (CBRNE) incidents or on terrorism. [9][10][11]13,14 Almost all studies concluded that HCW are not well prepared for disaster, regardless of staff group, clinical setting, and geographical region, and most studies called for more training.…”
mentioning
confidence: 99%
“…Over the past 2 decades, numerous studies on various aspects of HCW disaster preparedness, including knowledge, experience, drill participation, awareness of the disaster plan, perceived preparedness, and willingness to respond, etc. have been published 3 14 Most studies were surveys conducted in North America, Europe, and Australasia and many focused on chemical, biological, radiological, nuclear, and explosive (CBRNE) incidents or on terrorism 9 …”
mentioning
confidence: 99%
“…The survey identified that 50% of doctors did not know where to report for a mass casualty incident response. A similar cross-sectional national survey of 1500 acute healthcare providers in New Zealand showed that 58.1% of responders were aware of their role in a mass emergency event 18. Factors affecting perception of preparedness of healthcare staff for disaster response have been surveyed in the USA.…”
Section: Awareness Of Major Incident Preparednessmentioning
confidence: 99%